2015
DOI: 10.1093/hmg/ddv461
|View full text |Cite
|
Sign up to set email alerts
|

New function ofTSGA10gene in angiogenesis and tumor metastasis: a response to a challengeable paradox

Abstract: Several studies have shown that testis-specific gene antigen (TSGA10) could be considered as a cancer testis antigen (CTA), except for one study which has identified it as a tumor suppressor gene. In order to exert its function, TSGA10 interacts closely with hypoxia inducible factor (HIF-1α) and since this interaction is still not completely defined, the exact role of TSGA10 in angiogenesis and invasion is also under question. The current study was conducted to investigate the function of TSGA10 gene and evalu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 44 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…TSGA10 gene in human localizes to region q11.2 of chromosome 2 and is mainly expressed in testis and some tumors (Behnam et al, 2009, Mobasheri et al, 2007, Modarressi et al, 2004, Modarressi et al, 2001. In recent years, intense efforts to identify the function of TSGA10 led to the discovery of the inhibitory effect of TSGA10 on tumor angiogenesis (Mansouri et al, 2016). Previous studies have shown that TSGA10 is expressed during spermatogenesis (in testis), embryogenesis (undifferentiated embryonic stem cells), brain development, and in different types of cancer (Behnam et al, 2009, Miryounesi et al, 2014, Mobasheri et al, 2007, Mobasheri et al, 2006, Reimand et al, 2008, Smith et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TSGA10 gene in human localizes to region q11.2 of chromosome 2 and is mainly expressed in testis and some tumors (Behnam et al, 2009, Mobasheri et al, 2007, Modarressi et al, 2004, Modarressi et al, 2001. In recent years, intense efforts to identify the function of TSGA10 led to the discovery of the inhibitory effect of TSGA10 on tumor angiogenesis (Mansouri et al, 2016). Previous studies have shown that TSGA10 is expressed during spermatogenesis (in testis), embryogenesis (undifferentiated embryonic stem cells), brain development, and in different types of cancer (Behnam et al, 2009, Miryounesi et al, 2014, Mobasheri et al, 2007, Mobasheri et al, 2006, Reimand et al, 2008, Smith et al, 2011.…”
Section: Discussionmentioning
confidence: 99%
“…HIF-1a activates the transcription of genes involved in critical aspects of cancer development, such as angiogenesis and cell survival (Semenza, 2003). A recent study has shown that TSGA10 overexpression decreases HIF-1a transcriptional activity and inhibits angiogenesis, cell growth, and invasion of HeLa cells (Mansouri et al, 2016). Although these studies support the concept that TSGA10 has a repressive role in angiogenesis, these are still insufficient to explain the precise role of TSGA10 particularly in a living organism.…”
Section: Abstract: Zebrafish Tsga10 Angiogenesis Developmentmentioning
confidence: 99%
“…Cells were monitored after 48 hours. Sprouts formation was measured using NIH Image J software and presented as a percentage …”
Section: Methodsmentioning
confidence: 99%
“…Angiogenesis is also of great importance during pathological conditions like diabetic retinopathy, cancer development and chronic inflammatory diseases such as rheumatoid arthritis (RA) and psoriasis where excessive angiogenesis contributes to pathology . Angiogenesis is essential for tumor growth and metastasis and it has been shown that without angiogenesis malignant epithelial tumors could not grow more than several cubic millimeters . Malignant tumors need to recruit new blood vessels for their growth, invasion, and metastasis .…”
Section: Introductionmentioning
confidence: 99%
“…RASTEGARI-POUYANI ET Al. been shown that without angiogenesis malignant epithelial tumors could not grow more than several cubic millimeters. 5 Malignant tumors need to recruit new blood vessels for their growth, invasion, and metastasis. 6 There is strong evidence demonstrating the association between angiogenesis and inflammation in pathological conditions such as diabetes, rheumatoid arthritis (RA), psoriasis, Crohn's disease and finally cancer.…”
mentioning
confidence: 99%